Schistosoma mansoni IgG antibody response and Kato-Katz infection among pre-school aged children in Mbita, Western Kenya 2012-2014 - Arnold, Benjamin; Kanyi, Henry; Njenga, Sammy; Rawago, Fredrick; Priest, Jeffrey; Secor, W. Evan; Lammie, Patrick; Won, Kimberly; Odiere, Maurice (Dryad, 2020)
We compared serological measures of transmission based on antibody
response to S. mansoni soluble egg antigen (SEA) with stool-based measures
of infection among 3,663 preschool-age children in an area endemic for S.
mansoni in western Kenya. We estimated force of infection among children
using the seroconversion rate examined how it varied geographically and by
age.
The analysis included 3,663 children ages 2 months to 5.5 years who were
originally enrolled from 30 communities that participated in a cluster
randomized controlled trial to measure the effect of community-wide versus
school-based mass distribution of praziquantel to reduce S. mansoni
infection in Mbita, western Kenya. Villages were selected within 5 km of
Lake Victoria from among those with ≥ 25% S. mansoni prevalence that had
not received mass treatment with praziquantel. Preschool age children ≤5
years were assessed annually from 2012-2014 in repeated cross-sectional
surveys that collected blood and stool specimens, and samples were tested
for the presence of infection (in stool) and for antibodies to S. mansoni
soluble egg antigen (SEA).
This repository includes data and replication files to reproduce the
analyses in the manuscript entitled Fine-scale heterogeneity in
Schistosoma mansoni force of infection measured through antibody response
The materials in this repository are cross-linked with the Open Science
Framework (https://osf.io/rnme8/) and with GitHub
(https://github.com/ben-arnold/mbita-schisto). The data subdirectory
includes the datasets for the analysis. The R subdirectory includes all
computational notebooks, organized by display item. To re-run the
analyses, clone the GitHub directory (above), and create a new output
subdirectory alongside data and R to store the output files. Each dataset
includes a codebook. We have not included lon/lat village coordinates
under guidance from our IRB, so the notebook that creates Figure 1, Figure
S2 and Figure S3 cannot be run on the publicly available data (though the
source code and HTML output are in the repo) If you have any questions
about these files, please contact Ben Arnold at UCSF
(ben.arnold@ucsf.edu).